Carbon Dioxide and Carbon Monoxide Gas Detection System for Cars (ELEKTRIKA- Journal of Electrical Engineering, 2021)
: This paper report on a carbon dioxide and carbon monoxide gas detection system for cars. MQ7 and MQ135 are connected to ESP32 to detect carbon monoxide (CO) and carbon dioxide (CO2) respectively in this system. The numerical reading of the CO and CO2 are calculated in particles per million (ppm) and is displayed on a LCD. The real time result will also display on the Blynk mobile application. When the concentration of gases reaches a certain limit (1500ppm for CO2 and 35ppm for CO) the buzzer will on and an alert message will send to the mobile device informing the passenger on the danger. The aim of the system is to monitor the concentration of CO and CO2 in the car and enhanced the safety of the passenger in car.